Importance of representative metallurgical sampling and testwork programmes to reduce project risk – a gold case study. Issue 4 (2nd October 2019) - Dominy, Simon C.; O'Connor, Louisa; Purevgerel, Saranchimeg
ABSTRACT: When developing a process flowsheet, the risks in achieving positive financial outcomes are minimised by ensuring representative metallurgical samples and quality testwork. A case study is presented based on an underground gold operation, where poor metallurgical sampling led to grade and recovery underperformance. Sampling-related issues included: poor liaison between geologists and metallurgists; poor domaining; too few metallurgical samples collected and tested; unrepresentative sample composites and sub-samples; poor laboratory practice; and a lack of documentation and QAQC. These issues led to disruption over four years and are estimated to have cost around US$115M in lost revenue and US$7.5M in corrective expenditure. After an initial characterisation programme, a variability mini-bulk sampling and testwork phase was undertaken. This was followed by a pilot programme, progressing to trial mining and production. The paper emphasises the need for fit for purpose metallurgical sampling and testwork, and the early application of variability sampling.